Gem-difluoromethylated and trifluoromethylated derivatives of DMDP-related iminosugars: synthesis and glycosidase inhibition. Issue 7 (21st January 2016) - Li, Yi-Xian; Kinami, Kyoko; Hirokami, Yuki; Kato, Atsushi; Su, Jia-Kun; Jia, Yue-Mei; Fleet, George W. J.; Yu, Chu-Yi
Abstract : Gem -difluoromethylated and trifluoromethylated derivatives of DMDP-related iminosugars have been synthesized from cyclic nitrones and assayed against various glycosidases. Abstract : Gem -difluoromethylated and trifluoromethylated derivatives of DMDP-related iminosugars have been synthesized from cyclic nitrones12, 13, 18, ent -18 or23 and nitrone-derived aldehydes20 or ent -20 . The fluorinated iminosugars were assayed against various glycosidases, and ent -8 showed moderate but selective α-l -rhamnosidase inhibition. Difluoro or trifluoro units influenced the inhibitory activities of iminosugars in a more complex manner than single fluoro substitution. This may be correlated with their highly hydrophobic character and strong electron-withdrawing effect.